Vocational awareness through the use of simulation - Pawlovich, Walt E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The writer examines the literature to determine the central reasons for the failure of traditional methods of disseminating vocational information. The lack of readiness to receive information by adolescents is cited as one of the major problems in career education today. Several innovative techniques are discussed with an emphasis on simulation techniques. The writer expresses enthusiasm toward the implementation of simulation techniques and presents arguments for their potential benefits in promoting vocational awareness among today's youth.